PENGARUH PEMAHAMAN PERPAJAKAN, LOVE OF MONEY DAN DISKRIMINASI PERPAJAKAN TERHADAP PERSEPSI MAHASISWA MENGENAI TAX EVASION: (Studi Empiris pada Mahasiswa Program Studi Sarjana Akuntansi S-1 Konsentrasi Perpajakan Universitas Pamulang) - Kodirun, Eka Eka Putra; Juitania, Juitania (Postgraduate Management Journal, 2025)
The aim of this research is to analyze the influence of understanding taxation, Love of Money and tax discrimination on student perceptions regarding Tax Evasion. This type of research is quantitative research with primary data sources. The population in this study were Pamulang University students with a Taxation Concentration Accounting Study Program. The sample selection method used in this research was random sampling so that the final sample used was 321 students. Test the quality of the data using validity and reliability tests and use IMB SPSS 25, after that the classical assumption test is carried out, namely the normality test, multicollinearity test and hecteroscedasticity test, after that the hypothesis test. The results of this research show that understanding taxation, Love of Money and tax discrimination simultaneously influence student perceptions regarding Tax Evasion. Partially, it shows that Tax Discrimination influences Student Perceptions Regarding Tax Evasion. Meanwhile, Understanding Taxation, Love of Money does not influence student perceptions regarding Tax Evasion carried out on Pamulang University students in the Taxation Concentration Accounting Study Program. Keywords: Student Perceptions Regarding Tax Evasion, Understanding of Taxation, Love of Money and Tax Discrimination.